Knowledge of breastfeeding and associated factors in lactating mothers with children below 6 months old in 2023 at E Hospital, Hanoi, Vietnam - Uyen, Nguyen Thi Thu; Anh, Nguyen Thi Ngoc; Phuong, Le Thi Thu; Mai, Ninh Thi Phuong; Quy, Truong Van (Tạp chí Nghiên cứu Y học, 2025)
Breastfeeding is a natural and effective way to protect mothers‘ and children‘s health. This research aims to evaluate knowledge of breastfeeding among mothers with their children under 6 months old visiting the E Hospital, a tertiary hospital in Hanoi, Vietnam. A cross-sectional study was conducted using a predesignated, self-administered questionnaire based on the recommendation from the WHO. A special scaling system was employed to calibrate between different types of questions. Data was collected from the survey from 1/2023 to 10/2023 using the platform REDCap and analyzed using the software SPSS®. Among 150 women voluntarily participating in this research, only 7% have good knowledge of breastfeeding. A majority of participants understood the importance of breastfeeding, the consequences when children are not breastfed properly, how to use thawed breast milk and breastfeeding in special cases. On the other hand, most mothers did not have good knowledge of colostrum and mature milk characteristics, how to maintain and protect breast milk supply, and how to express and store breast milk after expression. The level of breastfeeding knowledge was not significantly associated with maternal age group, ethnicity, or residential area. Moreover, multiparity did not contribute to an improvement in breastfeeding knowledge (p > 0.05), contradicting prevailing beliefs in Vietnam.